(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Chaiphongpachara T, Laojun S. 2019. Using the modern morphometric approach to determine sexual dimorphism of three medically important flies (Order: Diptera) in Thailand. Biodiversitas 20: 1482-1486. This study assessed landmark-based geometric morphometric (GM) approach to determine sexual dimorphism of three medically important flies in Thailand, Chrysomya megacephala (Fabricius), Musca domestica (Linnaeus) and Boettcherisca nathani (Lopes). In the wing size analysis, the centroid size (CS) was computed to estimate the wing size. During wing shape analysis, shape variables were analyzed from principal components of partial warp scores calculated after generalized procrustes analysis of coordinates. Non-parametric permutation-based tests (1000 cycles) were used (after Bonferroni correction) at p < 0.05 for statistical comparisons of sizes and shapes between males and females in each fly species. The results of this study, analysis of wing size for sexual dimorphism based on wing CS did not find statistical differences in flies of any type (p > 0.05). However, not the size, the shape of the wings is a common factor used in identification of sexual dimorphism. The wing shape in all species was different between male and female sexes. These results have shown that the GM approach was effective in identifying the sexual dimorphism of C. megacephala, M. domestica and B. nathani, which is one way to help with sex differentiation in cases of incomplete specimens that cannot be classified by morphological methods.